Trends Studies’ Contributions For The Definition of the Fashion Brand’s Target (ModaPalavra e-periódico, 2018)
The effectiveness of Fashion Branding methodologies is closely related to the characteristics of your target audience. Thus, it is necessary to find methods to understand the consumer, in particular with regard to their motivations, habits, and preferences. Attracting the consumer's attention is to generate products that are able to satisfy the needs of an audience that lives the immediate. In the current society of the instant, where we all share information and we all reach an audience, understanding the dynamics of social influence and the motivations of consumption allows us to adapt the contents in such a way that they can be fully created to think about their final consumer. Therefore, the review of the literature on fashion, branding and trend studies leads to a cross-referencing and selection of information that, as a whole, will allow us to understand and define the target, through the definition of a persona, which represents the brand's ideal audience. This persona acts as a representation of the ideal target audience and can serve as a guideline when creating the products and contents of a brand. The aim is to study the audience and their motivations in a profound way first, in order to be able to create targeted products and brands. In this context, it is intended to give an explanatory and comprehensive approach to the component on the definition of the persona in said work, in order to clarify the utility thereof for the approximation of the brands to their audience.
Keywords: branding; trends; persona